2018
DOI: 10.1093/inthealth/ihy014
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of a human papillomavirus screen-and-treat model in Mwanza, Tanzania: training local healthcare workers for sustainable impact

Abstract: The screen-and-treat model for the identification and treatment of precancerous cervical lesions is an effective public health intervention with the potential to impact women by providing the tools and education needed by local healthcare professionals. However, limitations common to resource-poor settings, such as continuity of funding, loss to follow-up and transportation costs, remain barriers to sustainability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 7 publications
0
11
0
Order By: Relevance
“…Pre- and post-test knowledge showed significant improvement in recognition of signs and symptoms of cervical cancer. Bernstein et al reported similar results when training a group of 11 mid-level healthcare providers including nurses and clinical officers via a one-day classroom course, which was followed by supervised screen-and-treat practice during a mass screening campaign in Mwanza (Bernstein et al, 2018).…”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…Pre- and post-test knowledge showed significant improvement in recognition of signs and symptoms of cervical cancer. Bernstein et al reported similar results when training a group of 11 mid-level healthcare providers including nurses and clinical officers via a one-day classroom course, which was followed by supervised screen-and-treat practice during a mass screening campaign in Mwanza (Bernstein et al, 2018).…”
Section: Resultsmentioning
confidence: 85%
“…The cumulative VIA positivity was 9.2% (n = 4062) (Table 1). HIV infection was significantly associated with precancerous changes, with 16.8% of HIV+ women also VIA+ (523/3122) (Anderson et al, 2015; Bernstein et al, 2018; Dartell et al, 2014; Baldur-Felskov et al, 2018; Masalu et al, 2017; Chambuso et al, 2017; Kafuruki et al, 2013) (Table 2). High grade dysplastic lesions were often inferred by VIA screening results due to infrequency of pathologic confirmation.…”
Section: Resultsmentioning
confidence: 99%
“…The total number of VIA trainees was 2,722 providers, ranging from 3 [ 28 ] to 2216 [ 17 ], although we note two studies [ 25 , 27 ] did not report the number of trainees. The trainees included nurses [ 17 20 , 22 29 ], midwives [ 16 20 , 23 , 27 , 28 ], physicians [ 16 21 , 23 , 29 ], and other health care workers with less formal health education [ 18 , 19 , 24 , 25 , 30 ]. More information about the included studies is available in Table 2 .…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, one study [ 17 ] implemented a standardized 5-day training course for over 2000 trainees in Indonesia: the same training course was provided to doctors as well as community health workers. Three studies [ 24 – 27 ] organized training courses that lasted between 2 and 8 weeks to train the trainees in both VIA screening and new digital technology. Another study [ 29 ] included providers who had previously completed a 6-days training course and screened more than 50 women, before organizing a new training program focusing on technical training on smartphone-enhanced VIA.…”
Section: Resultsmentioning
confidence: 99%
“…A 2018 study examining cervical cancer awareness among women in Tanzania specifically noted that women who were least likely to be aware of cervical cancer and its risk factors were located in rural areas [11]. Increased burden of disease is related to the higher poverty rate, lower level of urbanization, low literacy rates, gender inequality, and poor access to healthcare services [5 ▪▪ ,23]. These factors can be applied on a regional level and attributed to the higher incidence of cervical dysplasia on Ukerewe Island in comparison to the relatively more developed metropolitan district on the mainland.…”
Section: Discussionmentioning
confidence: 99%